Charting the Unseen: How Non-Invasive Imaging Could Redefine Cardiovascular Prevention - Trimarchi, Giancarlo; Pizzino, Fausto; Paradossi, Umberto; Gueli, Ignazio Alessio; Palazzini, Matteo; Gentile, Piero; Di Spigno, Francesco; Ammirati, Enrico; Garascia, Andrea; Tedeschi, Andrea; Aschieri, Daniela (Journal of cardiovascular development and disease, 2024)
Cardiovascular diseases (CVDs) remain a major global health challenge, leading to significant morbidity and mortality while straining healthcare systems. Despite progress in medical treatments for CVDs, their increasing prevalence calls for a shift towards more effective prevention strategies. Traditional preventive approaches have centered around lifestyle changes, risk factors management, and medication. However, the integration of imaging methods offers a novel dimension in early disease detection, risk assessment, and ongoing monitoring of at-risk individuals. Imaging techniques such as supra-aortic trunks ultrasound, echocardiography, cardiac magnetic resonance, and coronary computed tomography angiography have broadened our understanding of the anatomical and functional aspects of cardiovascular health. These techniques enable personalized prevention strategies by providing detailed insights into the cardiac and vascular states, significantly enhancing our ability to combat the progression of CVDs. This review focuses on amalgamating current findings, technological innovations, and the impact of integrating advanced imaging modalities into cardiovascular risk prevention, aiming to offer a comprehensive perspective on their potential to transform preventive cardiology.